Australian Gallup Polls, December 1980 (ADA Dataverse, 2018)
Topics include: opinion of Ned Kelly, his life, his crimes and the hunt for him; whether the respondent approves of the law that radio and television stations cannot broadcast any election material 48 hours immediately before an election; whether results from opinion polls influence the way some people vote; taxation measures to keep personal taxation down; whether the respondent believes in God and life after death; religion of the respondent; when did the respondent last attend church; whether the respondent's links to religion are stronger or weaker now than in the past; whether the major ideas of the respondent's religion are stronger or weaker than they were; and for women whether she is responsible for all or most of the household shopping, whether she is employed, and approximately how much money is spent weekly on food and groceries. Background variables include: age; sex; marital status; level of education; country of birth; household composition (number persons in household, number children under age 5, number children between 5-12 years old, number children between 13 and 17 years old, age of the youngest person, and number of employed persons); whether respondent has moved in last two years; tenure of dwelling; occupation of self and head of household; voting enrolment; vote intention; income; and telephone ownership.